The Origin and Coupling Mechanism of the Magnetoelectric Effect in TMCl2-4SC(NH2)2 (TM = Ni and Co). (7th September 2014) - Mun, Eundeok; Wilcox, Jason; Manson, Jamie L.; Scott, Brian; Tobash, Paul; Zapf, Vivien S.
Abstract : Most research on multiferroics and magnetoelectric effects to date has focused on inorganic oxides. Molecule-based materials are a relatively new field in which to search for magnetoelectric multiferroics and to explore new coupling mechanisms between electric and magnetic order. We present magnetoelectric behavior in NiCl2 -4SC(NH2 )2 (DTN) and CoCl2 -4SC(NH2 )2 (DTC). These compounds form tetragonal structures where the transition metal ion (Ni or Co) is surrounded by four electrically polar thiourea molecules [SC(NH2 )2 ]. By tracking the magnetic and electric properties of these compounds as a function of magnetic field, we gain insights into the coupling mechanism by observing that, in DTN, the electric polarization tracks the magnetic ordering, whereas in DTC it does not. For DTN, all electrically polar thiourea molecules tilt in the same direction along the c -axis, breaking spatial-inversion symmetry, whereas, for DTC, two thiourea molecules tilt up and two tilt down with respect to c -axis, perfectly canceling the net electrical polarization. Thus, the magnetoelectric coupling mechanism in DTN is likely a magnetostrictive adjustment of the thiourea molecule orientation in response to magnetic order.